Competition between ferromagnetism and frustrated antiferromagnetism in quasi 2D Ce 2.15 (Pd1_xAgx) 1.95In0.9 alloys - Sereni, J.G (2016)
Fil: Sereni, J.G. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina